2022
DOI: 10.1029/2022jd037511
|View full text |Cite
|
Sign up to set email alerts
|

A Multimodel Investigation of Asian Summer Monsoon UTLS Transport Over the Western Pacific

Abstract: The Asian summer monsoon (ASM) as a chemical transport system is investigated using a suite of models in preparation for an airborne field campaign over the Western Pacific. Results show that the dynamical process of anticyclone eddy shedding in the upper troposphere rapidly transports convectively uplifted Asian boundary layer air masses to the upper troposphere and lower stratosphere over the Western Pacific. The models show that the transported air masses contain significantly enhanced aerosol loading and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 105 publications
(209 reference statements)
2
6
0
Order By: Relevance
“…The higher frequency of large-scale TST over the Asian monsoon region (>80% in some places) is consistent with recent studies that have shown the importance of monsoon dynamics in stratospheric moistening over Asia, where monsoon convection often moistens the upper troposphere but additonal monsoon-driven isentropic cross-tropopause transport is required to extend these impacts to the stratosphere (e.g., Randel et al, 2010;Pan et al, 2016;Honomichl and Pan, 2020;Pan et al, 2022). Alternatively, the lower percentages common throughout the rest of the Northern Hemisphere subtropics and extratropics suggest that direct convective moistening via overshooting is the primary driver of these extreme concentrations.…”
Section: Transport Characteristicssupporting
confidence: 89%
See 1 more Smart Citation
“…The higher frequency of large-scale TST over the Asian monsoon region (>80% in some places) is consistent with recent studies that have shown the importance of monsoon dynamics in stratospheric moistening over Asia, where monsoon convection often moistens the upper troposphere but additonal monsoon-driven isentropic cross-tropopause transport is required to extend these impacts to the stratosphere (e.g., Randel et al, 2010;Pan et al, 2016;Honomichl and Pan, 2020;Pan et al, 2022). Alternatively, the lower percentages common throughout the rest of the Northern Hemisphere subtropics and extratropics suggest that direct convective moistening via overshooting is the primary driver of these extreme concentrations.…”
Section: Transport Characteristicssupporting
confidence: 89%
“…Large-scale cross-tropopause transport can also be facilitated by isentropic assent along the warm conveyor belts of midlatitude cyclones, which has been shown to transport H 2 O and boundary-layer pollutants into the LMS (Roiger et al, 2011;Stohl, 2001;Wernli and Bourqui, 2002). Isentropic transport related to monsoon dynamics -which is intrinsically linked with smaller-scale monsoon convection -has also been shown to substantially contribute to LMS H 2 O enhancements (e.g., Randel et al, 2010;Pan et al, 2016;Honomichl and Pan, 2020;Pan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Although the three species show loosely correlated maxima in the UT indicating the influence of convectively lofted PBL pollution, their emission sources are quite different (e.g., Baker et al, 2012). With the relative short lifetime of 1-2 months (Duncan et al, 2007;Pan et al, 2022), CO is considered a good marker for convective transport. The CO maxima Geophysical Research Letters 10.1029/2024GL109256 near 13-14 km (360-370 K θ) indicate the level of convective outflow.…”
Section: Chemical Structures Of the Anticyclone Northern Edgementioning
confidence: 99%
“…These data, therefore, provide complementary information to the airborne activities from other parts of the ASM system. In particular, the recent airborne campaigns, StratoClim (http://www.stratoclim.org/) project conducted high‐altitude research flights over the southern flank of the ASM anticyclone (Bucci et al., 2020; Höpfner et al., 2019; Mahnke et al., 2021; von Hobe et al., 2021), and the ACCLIP campaign sampled the ASM air from the eastern edge of the anticyclone (Pan et al., 2022). These data also extend the existing sounding data from southern flank of the TP, which includes ozone, water vapor, particles, and clouds (Bian et al., 2012; Brunamonti et al., 2018; He et al., 2019; Ma et al., 2022; Yu et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Short‐lived halogenated species transported to the UTLS by this mechanism may delay the recovery of stratospheric ozone (Bednarz et al., 2022), with the modeled impact depending on the complexity of the chemical mechanism or treatment considered (Fernandez et al., 2021). The application of chemical and transport modeling techniques to predict ASM impacts on global atmospheric composition remains an active research area (e.g., Ploeger et al., 2017; Vogel et al., 2019; Yan et al., 2019; Pan et al., 2016, 2022; Clemens et al., 2023).…”
Section: Introductionmentioning
confidence: 99%